Simple Accounting Practices in Micro, Small, and Medium Enterprises: Praktik Akuntansi Sederhana di Usaha Mikro, Kecil, dan Menengah - Rafael , Mochammad Fani; Biduri, Sarwendah (Indonesian Journal of Law and Economics Review, 2025)
Abstract: Background: Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the Indonesian economy but often face challenges in implementing accounting practices. Specific Background: Many MSMEs still rely on simple and non-standard bookkeeping systems that do not comply with SAK EMKM standards. Gap: Limited research has explored how MSMEs perceive accounting and apply it in daily operations within local business contexts. Aim: This study aims to analyze business owners’ perceptions and describe how simple accounting is practiced in MSMEs. Results: Findings indicate that Citra Pertiwi Farm and SUGOfreshmilk maintain good daily bookkeeping routines, providing insight into cash flow and profitability. However, weaknesses remain in recording inventories and payables, and both enterprises do not apply full financial statements. Novelty and Implications: The study offers a real depiction of simple accounting practices, serving as a reference for improving financial literacy among small entrepreneurs. Highlights: The study explores real bookkeeping practices in small enterprises. It identifies key weaknesses compared to SAK EMKM standards. It provides insights for improving MSME financial literacy. Keywords: MSME Accounting Practices, Simple Bookkeeping System, Financial Perception, SAK EMKM Compliance, Financial Literacy